Informed Consent: Legal Procedure for Approval of Medical Action in Telemedicine - Helena Primadianti Sulistyaningrum; Ummu Kaidah Mutmainnah (Universitas Sriwijaya, 2026)
As technology continues to evolve, health services are increasingly integrating telemedicine into their practices. With the enactment of Law Number 17 of 2023 concerning Health, further study is required to address the legal issues arising from the provision of telemedicine services, particularly those relating to informed consent. This article aims to analyse the regulation of informed consent in telemedicine under Law Number 17 of 2023 concerning Health. The research employs a normative juridical method, drawing on legal materials such as legislation, legal literature, journal articles, and other relevant sources. The findings indicate that, despite the enactment of Law Number 17 of 2023 concerning Health and its implementing regulations, Indonesian positive law does not yet provide a specific procedural framework for informed consent in telemedicine services. This regulatory gap creates legal uncertainty and fails to provide adequate preventive legal protection. This article concludes that a telemedicine-specific regulatory framework, incorporating the six-stage procedural model developed in this study, is required to ensure legal certainty, strengthen legal protections for patients, medical professionals, and healthcare professionals, and establish clear procedural guidance for implementing informed consent in telemedicine services.